Traumatic brain injury options web application - Nagulavancha, Sruthi (Kansas State University, 2010)
According to the Division of Injury Response, Centers for Disease Control and Prevention, approximately 1.4 million Americans sustain a traumatic brain injury each year. The aim of the project is to create a web interface to link survivors, family members, and caregivers of individuals suffering from traumatic brain injuries (TBI) to potentially helpful agencies or service centers within their local communities. Often the TBI service centers located in the remote places are difficult to trace hence this website mainly concentrates on small rural centers which are located in Kansas State. The portal will offer two-dimensional and basic information about traumatic brain injury centers and specifically about access of resources. Within the portal, a link to an interactive map will be provided. A form for data entry helps the service centers to publish about their presence and the regions they serve. A search distance feature is also added into the website which interactively searches the nearest latitude, longitude values (TBI service center) to the user’s location by using the haversine formula.
Keywords: Web Application; Computer Science (0984)